V. O. Dorda, I. Shuliak. The translation of one-word metaphors in the computer discourse - V. O. Dorda; I. Shuliak (Philological Treatises, 2020)
The research deals with analyzing informal English in terms of information technologies, since nowadays the access to information has acquired a completely different form. English slang is widely presented in computer discourse; combining daily communication with the virtual communication, converting paper data into digital ones, changing forms of presentation, the invention of new means of communication are new elements of computer globalization. The authors study slangisms as metaphors, as they have many common features. The translation of slang has always been a hard task despite the huge number of existing software and corresponding CAT tools. Due to the popularization of computers, in the present day, computer slang and various types of metaphors play an important role in human communication.